Prevalence of low back pain and associated factors among office workers in Kano city, Nigeria - Salihu, Muhammad Nuhu; Lawal, Mamman Muhammad; Musa, Abuhuraira Ado; Abdullahi, Yusuf Muhammad; Umar, Maryam Dahiru; Amaka, Oruche Chinyere; Addi, Jacob Jonah; Muhammad, Faisal (International Journal of Research in Orthopaedics, 2021)
Background: Many studies across the globe have reported the prevalence of low back pain (LBP) among office workers. This study aimed to find out the prevalence of LBP and associated factors among office workers in Kano city, Nigeria. Methods: A cross-sectional type of study was conducted among the office workers in Kano metropolitan from September to December 2019. A total of 300 office workers were selected using a convenience sampling technique. The data was collected from the respondents by face-to-face interview technique using a semi-structured questionnaire and all the data collected were analyzed using statistical software (SPSS version 22.0). Results: In this study, the mean age of the respondents was 38.6±9.6 years and 72.7% of them were male. More than half (54.7%) of the respondents had a bachelor's degree and above. About 71.3% of the respondents had a familial history of LBP. About 68.0% of the respondents had suffered musculoskeletal disorder in the past and the majority (54.4%) mentioned they suffered hip pain. Only 33.7% of the respondents were maintaining the proper posture and 37.7% of the respondents were using an ergonomic chair. Conclusions: The findings of this study found a 65.3% prevalence of low back pain among the office workers in Kano metropolitan. Office workers should be encouraged to maintain proper postures at work and there is a need for more educational programs regarding the prevention measures of low back pain.